Some weighted statistical convergence and associated Korovkin and Voronovskaya type theorems - Braha, Naim L.; Srivastava, H. M.; Et, Mikail (Springer Heidelberg, 2021)
In this paper, we propose to investigate a new weighted statistical convergence by applying the Norlund-Cesaro summability method. Based upon this definition, we prove some properties of statistically convergent sequences and a kind of the Korovkin type theorems. We also study the rate of the convergence for this kind of weighted statistical convergence and a Voronovskaya type theorem.
Keywords: Weighted statistical convergence; Sequence spaces; Korovkin type theorem; Rate of convergence; Voronovskaya type theorem